Promoting the act of child helmet efficacy in Malaysia / Anisah Nur Abd. Rahman - Abd. Rahman, Anisah Nur (Faculty of Art and Design, 2015)
It is a known fact that for motorcyclist, a head protection is the most important piece of safety equipment to prevent yourself from getting much more worse injuries in an accident. Malaysians are found to have lack of self safety awareness moreover for the safety of the people that they love. This study goes some way in addressing the issue and suggesting a solution pertaining to the matter. The aim of this study is to identify Malaysian motorcyclists which are parents on their perception towards children's safety helmet in general. Most campaigns that was launched for motorcyclists are intended for adults, here is a campaign that is constructed and suggested for the main focus to be their children and their children's safety during motorcycle rides. A questionnaire was used to collect relevant data and 50 responses were analyzed. The preliminary results show that Malaysians motorcyclists that are parents are aware of the dangers that they put their children in when they do not provide safety helmets in general. Following an in-depth analysis, some recommendations for the study are presented.